Development of Islamic and ethnic educational videos using Android-based inspiring suite software - Septia Mulyana; Sirajul Munir; Jamilus Jamilus; Fadlan Muchlas Abrori (University of Muhammadiyah Malang, 2023)
Modifications of education and learning must be made because of the industrial revolution that continues to advance and develop so a teacher needs to prepare himself with science and teaching skills in the 21st century without losing the principles and character of traditional Islamic education. Likewise, with the use of media in learning, teachers are required to be able to innovate by utilizing existing technology so that students can get knowledge, expertise, or behavior from the results of the learning carried out. This research was conducted to develop educational videos using iSpring suite software that can be used in the face-to-face learning process, online learning, or independent learning, as well as to see its validity and practicality. The type of research used is research and development by applying 4D models (define, design, develop, and disseminate). The results showed that the educational videos that have been developed are needed by teachers and students and are declared very valid and very practical so that learning is more varied, interesting, and efficient and can be used independently or in groups anytime and anywhere without using the internet because it is in the form of an APK. For face-to-face learning, the learning media that has been designed is published in HTML while for self-study it into video form so that it can be opened on each student's Android.